Analysis of antioxidant additives-biodiesel blends on engine performance and emission characteristics of a diesel engine - Mohd Hafiz, Ali (2021)
Excess of oxygen content in biodiesel blends increased Nitrogen oxides (NOx) emission due to having a higher temperature combustion that can be mitigated by adding antioxidant additives into the blends. There is limited study conducted on the combustion, performance and emission characteristics of a diesel engine running on antioxidant additives-biodiesel blends that need a deeper understanding. This study aims to investigate the effect of antioxidant additives-biodiesel blends on engine combustion, performance, and emission characteristics of a single-cylinder direct injection diesel engine at a constant speed of 1800 rpm under various engine loads. A diesel fuel (DF), palm biodiesel blends (B20), B20 + 1000 ppm Butylated hydroxyanisole (BHA) antioxidant (B2HA1.0), B20 + 1500 ppm BHA antioxidant (B2HA1.5), B20 + 1000 ppm Butylated hydroxytoluene (BHT) antioxidant (B2HT1.0), and B20 + 1500 ppm BHT antioxidant (B2HT1.5) fuels are used in this study. Investigational works recorded cyclic combustion variations of cylinder pressure profiles of 200 consecutive cycles to assess the cyclic combustion variations. Those pieces of information were statistically evaluated to acquire the coefficient of variation (COV) for peak cylinder pressure (Pmax). At the same time, the engine performance and emission characteristics were analysed with response surface methodology (RSM) to develop a regression model. The finding shows a reduction in cylinder pressure and heat release rate by (0.47% - 5.78%) and (1.55% - 15.29%), respectively. COVPmax for antioxidant additives-biodiesel blends was discovered to be higher at a maximum of 36.36% than B20. The brake specific fuel consumption of antioxidant additives-biodiesel blends was reduced (2% - 15%), whereas brake thermal efficiency increased (7.4% - 36.0%) compared to B20. Furthermore, BHA antioxidant additives perform better in reducing NOx emissions, with the highest reduction average of 30.5%. However, a maximum increase of carbon monoxide (26.6%) and hydrocarbon emission increase (27.1%) were recorded compared to B20. Analysis of variance (ANOVA) of experimental result shows a 95% confidence level that indicates the developed models are significant with high correlation coefficients R2 for the various response variables. Hence, in this study, B2HA1.0 shows the most effective to reduce NOx emission but produces higher cyclic variations. In general, these results have donated an essential understanding of the antioxidant additives-biodiesel blends operating with engines and offer supplementary information to reduce NOx emissions.